Pengenalan Kosakata Bahasa Inggris Bertema Animals dan Fruits melalui Guessing Picture Game pada Siswa Kelas III SD - Rani Zahra; Vivi Amanda; Asih Ria Ningsih; Yesi Darmayanti; Khabib Muafi; Arisman Arisman; Tina Angriani Lubis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2026)
The low mastery of basic English vocabulary among elementary school students has become one of the challenges in the learning process, particularly in introducing vocabulary related to animals and fruits. Based on preliminary observations conducted at SD Negeri 008 Rambah, third-grade students still experienced difficulties in recognizing, remembering, and pronouncing simple English vocabulary. This PkM aimed to improve students’ English vocabulary mastery through the implementation of the Guessing Picture Game. The activity was conducted on March 9, 2026, involving 17 third-grade elementary school students. The implementation method was carried out through picture-guessing game-based learning using visual media with animals and fruits themes. Data collection techniques included observation, documentation, and learning evaluation, while data analysis employed a qualitative descriptive approach based on changes in students’ abilities before and after the activity. The results showed an improvement in students’ ability to recognize, remember, and pronounce English vocabulary. Students’ active participation, enthusiasm, and self-confidence also improved during the learning process among third-grade students of SD Negeri 008 Rambah.